Bladder tuberculosis: therapy and surgery - Ye. V. Kulchavenya; D. P. Kholtobin; Ye. V. Brizhatyuk (Бюллетень сибирской медицины)
Bladder tuberculosis is one of the most serious complication of nephrotuberculosis. Efficiency of current therapy is 42.1% only; it was a reason for creation of new scheme of etiopathogenetic therapy and surgical treatment. 63 patients were enrolled in study: 1st group received standard therapy and 2nd — modified. 9 patients from control group were operated with creation of neobladder. Results of therapy for patients treated with levofloxacin and trospium chloride were twice higher than after standard.